Mengajar Siswa Tingkat Dasar dalam Menuju Smart Village di Desa Cemagi, Kabupaten Badung, Bali - Anak Agung Ketut Sri Asih; Komang Fridagustina Adnantara; Sarita Vania Clarisa; Gusti Ayu Putu Manik Yulia Pramita; Francise Connie Angelina Gunawan (Pubfine Media Group, 2024)
The program of teaching elementary school students is one of the efforts by students to implement the Tri Dharma of Higher Education by contributing to the community. Triatma Mulya University organizes activities in Cemagi Village, Badung Regency, Bali, with the theme